PHYLOGENETIC RELATIONSHIPS AND TAXONOMIC REVIEW OF THE FAMILY SALAMANDRIDAE (AMPHIBIA: CAUDATA) FROM VIETNAM - Trường, Nguyễn Quảng (Vietnam Journal of Biotechnology, 2011)
Five species of the family Salamandridae are currently recognized from Vietnam: Paramesotriton deloustali from Lao Cai, Ha Giang, Tuyen Quang, Bac Kan, Quang Ninh and Vinh Phuc provinces; P.guanxiensis from Cao Bang province; Tylototriton asperrimus from Ha Giang and Lao Cai provinces; T.verrucosus from Lai Chau province; and T. vietnamensis from Bac Giang, Phu Tho, and Lang Son provinces. Specimens of Tylototriton species were collected from different localities in Northern Vietnam for phylogenetic analysis. Comparison of 450 base pairs of partial Cytochrome b mitochondrial DNA sequences shows 100% identity between Tylototriton aperrimus from Ha Giang and Lao Cai provinces. The same comparisons show 100% identity between specimens of Tylototriton vietnamensis from Bac Giang and Phu Tho provinces and 99.8% between specimens from Bac Giang and Lang Son provinces. This identity shows little geographic variation of conspecific species. However, the sequences of the T. asperrimus and T.vietnamensis from above localities showed an uncorrected pairwise sequence divergence of 8 - 8.3%. Diagnostic morphological characters of the five Vietnamese species are presented based on examined specimens or literature. Comparison of morphological characters between T. vietnamensis and T. hainanensis showed that the first species differs from the latter by having tip of forelimb reaching to nostril (tip of forelimb reaching to eye in T. hainanensis), snout-vent length shorter than tail length (snout-vent length longer than tail length in T. hainanensis). Furthermore, we provided additional data on the habitat and reproduction of Paramesotriton deloustali, Tylototriton asperrimus, and T. vietnamensis